Evaluation of Formalin-fixed Paraffin-embedded Tissue Samples Diagnosed by Histopathology as Echinococcus in Çorum - Yılmaz Baş; Yunus Emre Beyhan; Havva Hande Keser Şahin; Tuğba Özçerezci; Dursun Karasartova; Ayşe Semra Güreser; Güven Güney; Ayşegül Taylan Özkan (Türkiye Parazitoloji Dergisi, 2021)

(untitled)
Objective:This study aimed to detect the presence of Echinococcus spp. in formalin-fixed paraffin-embedded (FFPG) samples of hydatid cyst cases and to discuss the DNA isolation problems in FFPG samples.Methods:FFPG samples of 47 cases diagnosed with hydatid cyst were included in this study. Demographic characteristics of the cases were investigated. Microtome sections were taken from the samples and deparaffinization, DNA extraction, polymerase chain reaction (PCR), and gel agarose electrophoresis procedures were performed.Results:Of the cases, 55.3% were female, whereas 45.7% were male. Average age was 45.47 and 68.1% of the cases were located in the liver, 17.0% in the lung, 12.8% in the abdomen, and 2.1% in the brain. DNA was obtained in only 11 (23.4%) of the FFPG cyst samples and no proliferation was detected in the PCR products of any of the sample.Conclusion:The scolex/germinal membrane’ absence in the FFPG sections, intense inflammatory cell reaction, presence of fibrosis and stromal/parenchymal tissue, DNA damage due to formaldehyde action, long-term archiving, and insufficient amount of DNA obtained were considered as factors preventing DNA replication in PCR.